2016
DOI: 10.1080/10106049.2016.1213888
|View full text |Cite
|
Sign up to set email alerts
|

Road condition assessment by OBIA and feature selection techniques using very high-resolution WorldView-2 imagery

Abstract: Accurate information on the conditions of road asphalt is necessary for economic development and transportation management. In this study, object-based image analysis (OBIA) rule-sets are proposed based on feature selection technique to extract road asphalt conditions (good and poor) using WorldView-2 (WV-2) satellite data. Different feature selection techniques, including support vector machine (SVM), random forest (RF) and chisquare (CHI) are evaluated to indicate the most effective algorithm to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…It is a nonlinear metric derived from Pearson's chisquared test statistic, 22 and it creates a predictive model that minimizes the misclassifications. 32 The CHI 21 between two spectral signatures…”
Section: City Block Distancementioning
confidence: 99%
See 1 more Smart Citation
“…It is a nonlinear metric derived from Pearson's chisquared test statistic, 22 and it creates a predictive model that minimizes the misclassifications. 32 The CHI 21 between two spectral signatures…”
Section: City Block Distancementioning
confidence: 99%
“…23,26,27 The chosen hybrid spectral similarity measures are SID-SAM, 28 SID-SCA, 23 SID-CBD, 25 SID-EUD, 25 CHI-SAM, 25 CHI-SCM, JMD-CHI, 25 and SID-CHI. 29 The outcomes of the classifications are summarized using the confusion matrices and evaluated for overall accuracy (OA), [30][31][32][33][34][35] 38 coefficient of determination (R 2 ), mean absolute error (MAE), and root mean squared error (RMSE). The results revealed the multiclass classification capability of hybrid SSM where the SID-SCA performed well on hyperspectral image data (VNIR) of paper samples compared with other SSM.…”
mentioning
confidence: 99%
“…FS, which is regarded as a crucial task that influences the GEOBIA classification accuracy, specifies the most relevant features to increase the effectiveness of the adopted classification approach and expedites the processing time by minimizing irrelevant or redundant features [46]. Various FS algorithms have been incorporated with the GEOBIA approach in various applications, and these methods include RF [47,48], SVM [47], ant colony optimization (ACO) [49,50], artificial bee colony [51], hybrid particle swarm optimization [52], correlation-based FS (CFS) [49,53], and chi-square [54]. Ridha and Pradhan [49] applied three FS methods, namely, CFS, RF, and ACO, to discriminate several types of landslides from LiDAR data.…”
Section: Related Studiesmentioning
confidence: 99%
“…For mapping tasks using VHR data, object-based image analysis (OBIA) is preferred over traditional per-pixel classification [6][7][8][9][10], because pixels of a homogeneous land-cover patch often have heterogeneous spectral responses or high information content. Combined with various classification algorithms, OBIA has been routinely used to map detailed urban features with some success [4,11,12]. Previous studies also demonstrated the advantage of data fusion of VHR and LiDAR or synthetic aperture radar (SAR) images for urban-mapping applications [13][14][15].…”
Section: Introductionmentioning
confidence: 99%